2007
DOI: 10.1152/ajpregu.00547.2006
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of intravenous hyperosmotic solutes on drinking latency and c-Fos expression in the circumventricular organs and hypothalamus of the rat

Abstract: December 28, 2006; doi:10.1152/ajpregu.00547.2006.-Hyperosmotic intravenous infusions of NaCl are more potent for inducing drinking and vasopressin (AVP) secretion than equally osmotic solutions of glucose or urea. The fact that all three solutes increased cerebrospinal fluid osmolality and sodium concentration led the investigators to conclude that critical sodium receptors or osmoreceptors for stimulating drinking and AVP secretion were outside the blood-brain barrier (BBB) in the circumventricular organs (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…This study demonstrates that: 1) the concentration of ENaC-expressing neurons in the sensory CVOs greatly exceeds that found in nearby brain sites by ϳ2 times; 2) ENaC-expressing CVO neurons become c-Fos activated following intraperitoneal injections of hypertonic saline, while comparable injections of isotonic saline had no effect and these findings are in agreement with a previous study (22); 3) sodium deprivation induces c-Fos activation of ENaC-expressing neurons in the OVLT and SFO but has no noticeable effect in the AP; the latter result is different from what has been reported in sodium depletion experiment in which the diuretic drug furosemide was used to induce NaCl loss (35) perhaps because this drug blocks GABA-A receptors in the brain (29); 4) sodium repletion elicits c-Fos activation of ENaC-expressing neurons in all three sensory CVOs, especially in the AP; and 5) increases in c-Fos activity in the CVOs were correlated with increases plasma sodium concentration.…”
Section: Discussionsupporting
confidence: 93%
“…This study demonstrates that: 1) the concentration of ENaC-expressing neurons in the sensory CVOs greatly exceeds that found in nearby brain sites by ϳ2 times; 2) ENaC-expressing CVO neurons become c-Fos activated following intraperitoneal injections of hypertonic saline, while comparable injections of isotonic saline had no effect and these findings are in agreement with a previous study (22); 3) sodium deprivation induces c-Fos activation of ENaC-expressing neurons in the OVLT and SFO but has no noticeable effect in the AP; the latter result is different from what has been reported in sodium depletion experiment in which the diuretic drug furosemide was used to induce NaCl loss (35) perhaps because this drug blocks GABA-A receptors in the brain (29); 4) sodium repletion elicits c-Fos activation of ENaC-expressing neurons in all three sensory CVOs, especially in the AP; and 5) increases in c-Fos activity in the CVOs were correlated with increases plasma sodium concentration.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, water-deprived animals have increased motivation of drinking water (Stricker and Sved, 2000; McKinley and Johnson, 2004). Previous studies found that CVOs are the closest in relation with drinking water outside the BBB, such as SFO, MnPO and OVLT, which constitute nerve fibers network and contribute to the stability of osmotic pressure (Miselis, 1981; Ho et al, 2007). As compared to high urea or sugar, high osmotic pressure easily affects the CVO neurons, and ultimately retro-regulates animal’s thirst perception and water consumption to reduce plasma osmotic pressure (Noda and Sakuta, 2013; Oka et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The OVLT plays a major role in hyperosmolality-stimulated thirst (19,27,28,44,48) and pituitary release of vasopressin (30,44,48) and oxytocin (17,35). To date, however, involvement of OVLT in mediating hyperosmolality-induced increases of SNA has not been directly assessed.…”
Section: Discussionmentioning
confidence: 99%